design and realization of a smartphone game on the history and geography of the region (M’sila) - Hedjouli, Yacine; President: Tahri, Zohair (University of M'sila, 2021)
The project carried out during this end of studies, consists in developing a asmartphone game on the history and geography of the region (M’sila) The aim of this work is to achieve an enjoyable and easy application, equipped with the necessary functionalities and adapted to the needs of our project. Our project aims to provide self-motivated users with options for learning in gaming environment . our applications is presented in form of quiz application wich try to deliver historical as well as geographical informations related to our state (M’sila) To implement our solution, we opted,UML as a modelling language, DART as a programming language by using it in the FLUTTER cross platform service under the ANDROID STUDIO platform
Keywords: design , realization , a smartphone game , history , geography , M’sila